Women's Health and Reproductive Health Needs of Lesbian Individuals in Türkiye - Güney, Demet; Demirezen, Esma (Ordu University, 2024)
Health is a basic right that all individuals have from birth. The World Health Organization defines reproductive health as a state of complete mental, physical, social well-being, and not merely the absence of disease or impotence, in all matters relating to the reproductive system, its functions, and processes. Reproductive health services include the freedom to have children, fertility, adolescent sexuality, unwanted pregnancies, unhealthy abortions, maternal and infant mortality, related disabilities, HIV/AIDS, and sexually transmitted diseases. LGBTQI+ includes different gender identities, and sexual orientations including lesbian, gay, bisexual, transgender, queer, and intersex. Gender is assigned at birth, based on chromosomal, hormonal, physical, or anatomical characteristics. However, sexual orientation is defined as the gender to which one's sexual impulses are oriented or the ongoing emotional, romantic, and sexual attraction to an individual of a particular gender. These groups face important existential problems, especially in developing, traditional lifestyle predominate countries or in Muslim countries like Türkiye. STDs and HIV/AIDS are among the diseases that can be treated in the lesbian population through expanded RHS. General gynecological, breast cancer should also be considered in protecting, and improving lesbian individual’s health. This study draws attention to women's health problems in Türkiye, including breast cancer and other gynecological health problems, as well as reproductive health problems of lesbian individuals. It aims to share LGBTI+ health care problems and in this context, to emphasize the women's health and reproductive health needs of midwives and nurses, lesbian individuals in Türkiye, which are generally practiced as a female profession in Türkiye.
Keywords: 5. Gender equality; 10. No inequality; 16. Peace & justice; 3. Good health